Perancangan Alat Pencelupan Benang untuk Meningkatkan Kapasitas Produksi pada Proses Pencelupan Benang pada UMKM H. Muslikun - Zain, Badrus Sibyan; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
UMKM H. Muslikun is a business that produces traditional woven sarongs. In the production process, the yarn dyeing process is one of the important processes and has an influence on the products produced. In this yarn dyeing process, manual tools are still used, and the position is less ergonomic because the worker bends slightly, besides that the production capacity that can be produced is still quite small. This results in workers feeling less comfortable and the need for threads being unable to be met if at any time there is an increase in demand due to increased production. Therefore, from this, in this research a yarn dyeing tool will be created that is in accordance with ergonomics using anthropometric methods with the aim of making workers comfortable and increasing production capacity in the yarn dyeing process. From anthropometric data processing, the machine dimensions are 100 cm high and 58 cm wide. From the test results, it was found that the capacity of yarn that could be dyed was 160 rolls from the previous 150 rolls of yarn.